A Psicologia do trabalho e das organizações na formação do psicólogo no Brasil - Lima, Fellipe Coelho (2013)
This research has aimed to analyze the presence of the Work and Organizational Psychology (WOP) at the psychologist s undergraduate education after 2004 s National Curricular Guidelines in Brazil. It has investigated in 43 Brazilian undergraduate courses of Psychology how their Course Pedagogical Projects (CPPs) approach the WOP issues. For that investigation, the CPPs, the subjects programmes related to the WOP and the curriculum grid have been accurately read and analyzed. Categories created by similar studies have also been used. The studied knowledge field has been cited by 41 courses, mainly on the definition of the egress s professional profile, on the expected competences and on the psychologist s formation process lines. Moreover, 28 courses have disposed curricular emphasis on the WOP and 12 have provided professional practices on that Psychology s field. All the courses have displayed, at least, one subject related to the WOP and in 29 cases there have been found between two and six subjects concerned to that field of Psychology, occupying nearby 10% of the whole courses credit hours. It has been verified that the Work and Organizational Psychology is allied to discussions about Quality of Life and Health of the Worker, bonded to work prescriptions at the Personnel Management departments and in other places such as syndicates. Additionally, 37% (147) of the WOP s subjects concerns to the contents of the Work Psychology, 21% (81) relates to the Organizational Psychology, 18% (71) are about Industrial Psychology s topics and 14% (55) debates the field generically. The most often issues are: Recruitment and Selection (25 courses); Training, Development, Learning and Education (24); and Work and Mental Health (24). Those topics have assumed three functions: providing principles for the acting at the WOP field; tutoring psychologists to analyze their own workplaces; and offering a comprehension of the human being mediated by the Work. It has been concluded that the WOP is incorporated on the psychologist s undergraduate education by considering the increasing of its presence and the occurrence of its traditional and emergent topics